Factors Associated with Rabies Antibody Titers in Dogs in Mapanget District, Manado City - Dimitris Rosalin Hutasoit; Billy Johnson Kepel; Jeanette Iren Christy Manoppo (International Journal of Health and Pharmaceutical (IJHP), 2026)
Rabies remains a highly fatal zoonotic disease and continues to pose a substantial public health challenge in Indonesia, including in Manado City. Mapanget District hosts a considerable dog population, yet empirical data on herd immunity based on rabies antibody titers are scarce. This study aimed to evaluate the determinants associated with rabies antibody titers among dogs in Mapanget District, Manado City. A cross-sectional study was conducted involving 97 dogs selected through purposive sampling. Serum samples were analyzed using the Enzyme-Linked Immunosorbent Assay (ELISA) to classify antibody titers as protective (≥0.5 IU/mL) or non-protective (<0.5 IU/mL). Statistical analyzes included Fisher's Exact Test and multivariable logistic regression to assess associations between host factors and antibody titer status. Only 8.2% of dogs exhibited protective antibody titers, whereas 91.8% demonstrated non-protective levels. Vaccination status showed a highly significant association with antibody titers (p < 0.001). Vaccinated dogs were markedly more likely to achieve protective titers compared to unvaccinated dogs (OR = 35.71; 95% CI: 3.888–328.026). No significant associations were observed for dog type, age, or sex (p > 0.05). The findings underscore a critically low level of immunity within the dog population in Mapanget District, primarily attributable to insufficient vaccination coverage. Vaccination emerged as the predominant factor influencing the development of protective antibody titers. Strengthening routines and mass vaccination programs, coupled with systematic serological monitoring, are imperative to achieve adequate herd immunity and to advance rabies elimination strategies in the region.